Changes in coordination variability with skill development in expert performers - Wilson, C.; Simpson, S.; Hamill, J.; van Emmerik, R. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The purpose of this study was to investigate the influence of skill level, in triple jumping, on the coordination variability of lower extremity intra-segmental couplings. Relative motion plots and a modified vector coding technique were utilised to quantify the coordination variability across the trials. The results suggest that coordination variability in expert performers follows a U-shape curve as skill level increases. Higher levels of coordination variability were observed in the most and least experienced performers with relatively lower levels observed in the subjects with moderate levels of experience. This study has highlighted the need for addressing the learning effect when analysing coordination variability from a dynamical systems perspective.